Multidimensional phenomena of Hajj: study of Javanese pilgrims - M Zulfa (Indonesian Journal of Islam and Muslim Societies, 2015)
Performing Hajj pilgrimage to Mecca is the fifth pillar of Islam, whereas thesefive pillars of Islam are believed by all Muslims in the world as the foundationof Islam. Hajj is a must for any Muslim who has all the abilities, in term offinancial, physical, as well as psychological, to perform it, This paper is areport of a research on various aspects accompanying the accomplishment ofthe Hajj pilgrimage to Mecca by the pilgrims. Those aspects are the spiritualteologic,the psychological, the sociological, and the economic. The objectsof the research were the city of Salatiga, the District of Semarang, and theDistrict of Magelang. The spiritual-teologic aspect is used to explain the levelof religiousity of a Muslim performing the Hajj while the psychological aspectis related to the psycho-condition, mental, and desires experienced or possessedby the pilgrims. The sociological aspect is the social faithfulness, thesocial harmony supported by those pilgrims. Last but not least, the economicaspect is the motive of the pilgrims to increase their prosperity or their economicpower. By implementing the descriptive-qualitative approach, this researchaimed at providing objective, accurate, and systematic depictions ofthose issues related with the objects of the research. For the data collection,the researcher used various methods such as observation, interview, and documentation.The data was then analyzed through the descriptive qualitativequantitativeapproach. The result shows that the spiritual-teologic, the psychological, the sociological, as well as the economic aspects are all present inthe accomplishment of the Hajj, with the spiritual-teologic and the psychologicalaspects play the most dominant roles. The quantitative analysis showsthat there is a significant influence of the spiritual-teologic and the psychologicalaspects toward the completion of the Hajj of the pilgrims. It is provenwith the statistical calculation that the degree of significant is 1% and 5%that shows that the r sum is bigger than the r table or that 0,599 0,3450,266. Meanwhile, the descriptive analysis of the data shows that the spiritual-teologic and the psychological aspects are the more dominant aspectscompared to the sociological, as well as the economic aspects.Haji merupakan rukun Islam yang ke lima, sementara rukun Islam dijadikansebagai pondasi dasar agama oleh seluruh umat Islam di dunia. Setiap muslimyang telah mampu, hukumnya wajib menunaikan ibadah haji. Baik mampusecara financial maupun mampu secara fisik ataupun psikis. Tulisan inimerupakan hasil penelitian yang menfokluskan beberapa aspek yang menyertaijama’ah haji. Aspek-aspek itu meliputi: aspek teologis-spiritual, aspek psikologis,aspek sosiologis dan yang terakhir aspek ekonomis dengan mengambil objekpenelitian di Kota Salatiga, Kab. Semarang dan Kab. magelang. Aspek teologisspiritualadalah aspek yang menjelaskan mengenai tingkat religiusitas seseorangsecara individu ketika melaksanakan ibadah haji, sedangkan aspek psikologisyaitu, aspek yang berhubungan dengan psikis, mental, keinginan-keinginandialami yang dirasakan oleh jama’ah haji. Selanjutnya aspek sosiologis,merupakan kesalehan sosial, hubungan kemasyarakatan yang dilakukan olehjama’ah haji. Dan yang terakhir aspek ekonomis, yaitu motif jama’ah dalammelakukan ibadah haji adakah faktor atau keinginan meningkatkan ekonomi.Dengan menggunakan pendekatan deskriptif-kuantitatif penelitian ini bertujuanuntuk mendapatkan gambaran yang objektif, akurat dan sistematis, mengenaimasalah-masalah yang ada di objek penelitian. Untuk mengumpulkan datadigunakan beberapa metode yaitu, observasi, interview dan dokumentasi.Kemudian data yang telah terkumpul dianalisis menggunakan pendekatandeskriptif kualitatif-kuantitatif. Hasil penelitian menunjukkan bahwa aspekteologis-spiritual, aspek psikologis, aspek sosiologis dan aspek ekonomismenyertai para jamaah haji terutama aspek spiritual dan psikologis. Dari analisissecara kuantitatif menunjukkan adanya pengaruh signifikan aspek teologis-spiritualdan aspek psikologis terhadap jama’ah haji. Hal itu dibuktikan dengan hasil perhitungan statistik pada taraf signifikansi 1% dan 5% menunjukkanbahwa r hitung lebih besar dari r tabel yaitu: 0,599 0,345 0,266. Sedangkananalisis deskriptif menghasilkan bahwa aspek teologis-spiritual dan aspekpsikologis adalah aspek yang lebih menonjol jika dibandingkan dengan aspekaspek-aspek lainnya, dibanding aspek sosiologis dan aspek ekonomis.